Title says it all, I simply want to know exactly how to element $(x+y)^4+x^4+y^4$. Ns only understand that it"s feasible to factor, yet got no idea how to perform it. If it to be a single-variable polynomial i could shot to uncover rational roots or something, but I"m lost with this one.

You are watching: Factor x^4-y^4


*

*

Note the $$(x+y)^4 + x^4 + y^4 = y^4 ((x/y+1)^4 + (x/y)^4 + 1)$$and see if friend can element $((t+1)^4 + t^4 + 1$. Over there is a quadratic factor.


*

This is a symmetric polynomial in $x$ and $y$, for this reason it can be expressed, by Newton"s theorem, as a polynomial in $s=x+y$ and also $p=xy$.

Indeed $x^2+y^2=(x+y)^2-2xy=s^2-2p$, whence$$x^4+y^4=(x^2+y^2)^2-2x^2y^2=(s^2-2p)^2-2p^2=s^4-4ps^2+2p^2.$$Therefore$$(x+y)^4+x^4+y^4=2s^4-4ps^2+2p^2=2(s^2-p)^2=2(x^2+xy+y^2)^2.$$

$x^2+xy+y^2$ is irreducible in $altoalsimce.orgbf R$, however factors in $altoalsimce.orgbf C$ as$$(x-jy)(x-j^2y)quad extwhere j;  extand j^2 ; extare the non-real cubic roots of unity.$$


*

*

Beyond what I have actually posted, it can not be factored in the actual field. If you want to aspect it in the complicated field, you have to learn exactly how to settle a quartic equation since you essentially need to know that root of $(t+1)^4 + t^4 + 1 = 2t^4 + 4t^3 + 6t^2 + 4t + 2 = 0$, it deserve to be simplified to $t^4 + 2t^3 + 3t^2 + 2t + 1 = 0$.Lucky enough, this is same to $(t^2 + t + 1)^2$

Thus $x^4 + y^4 + (x + y)^4 = (x^2 + xy + y^2)^2$.No additional factorization is easily accessible in the genuine field...

Best desire


I know that using complex algebra, us can factor $x^4 + y^4 = (x^2 + y^2 + sqrt2xy)(x^2 + y^2 - sqrt2xy)$. I have no idea how to proceed forward...Good luck


I am sorry, there is a slight mistake, i forgot factoring 2. For this reason $x^4 + y^4 + (x+y)^4 = 2(x^2 + xy + y^2)^2$


$$(x+y)^4+x^4+y^4=(x^2+y^2+2xy)^2+(x^2+y^2)^2-2(xy)^2=\<(x^2+y^2+2xy)^2-(xy)^2>+<(x^2+y^2)^2-(xy)^2>=\(x^2+y^2+xy)(x^2+y^2+3xy)+(x^2+y^2+xy)(x^2+y^2-xy)=\(x^2+y^2+xy)(2x^2+2y^2+2xy)=2(x^2+y^2+xy)^2$$


$$x^4 + y^4 + (x + y)^4=2 x^4 + 4 x^3 y + 6 x^2 y^2 + 4 x y^3 + 2 y^4$$$$=x (x (x (2 x + 4 y) + 6 y^2) + 4 y^3) + 2 y^4=2 x^4 + y (4 x^3 + y (6 x^2 + y (4 x + 2 y)))$$$$=4 y^2 (x^2 + x y) + 2 (x^2 + x y)^2 + 2 y^4=2 (x^4 + 2 x^3 y + 3 x^2 y^2 + 2 x y^3 + y^4)$$$$=2 (x^2 + x y + y^2)^2$$


Thanks because that contributing response to altoalsimce.orgematics Stack Exchange!

Please be sure to answer the question. Provide details and share your research!

But avoid

Asking because that help, clarification, or responding to other answers.Making statements based upon opinion; earlier them up with referrals or an individual experience.

Use altoalsimce.orgJax to format equations. altoalsimce.orgJax reference.

See more: What Happened To Tim On Dog The Bounty Hunter, Tim Chapman

To discover more, watch our advice on writing an excellent answers.


short article Your prize Discard

By click “Post your Answer”, girlfriend agree come our regards to service, privacy policy and cookie policy


Not the prize you're looking for? Browse other questions tagged factoring or questioning your own question.


site design / logo design © 2021 ridge Exchange Inc; user contributions licensed under cc by-sa. Rev2021.11.10.40696


your privacy

By click “Accept all cookies”, friend agree ridge Exchange can store cookies on your maker and disclose details in accordance with our Cookie Policy.